Analisis Faktor-Faktor yang Mempengaruhi Underpricing Saham pada Penawaran Umum Perdana (Initial Public Offering) di BEI Tahun 2020-2022 - Wildan Rafendra; Rusmiyatun Rusmiyatun; Nur Edi Cahyono (STIE Rajawali Purworejo, 2025)
This study aims to analyze the factors that influence stock underpricing in initial public offerings on the Indonesia Stock Exchange (IDX), from 2020 to 2022. This study analyzes the factors that influence underpricing which consist of variables of Underwriter Reputation, Company Age, Return On Asset and Financial Leverage in initial public offerings (IPOs). By using purposive sampling method, the number of samples in this study were 48 companies. Data analysis used Partial T Test and Simulant F Test (F-Test). The partial t test results show that IPO stocks on the IDX have a negative effect on underpricing, only Financial Leverage has a positive effect on underpricing. The F-Test results found that only the independent variables Underwriter Reputation, Company Age, Return On Assets and Financial Leverage have a significant effect on underpricing. The coefficient of determination shows 66.6%, indicating that the ability of the independent variables of underwriter reputation, company age, return on assets and financial leverage to the dependent variable underpricing is 66.6% while 33.4% is explained by other variables such as company size, earnings per share, return on equity, percentage of shares offered.